2015
DOI: 10.1016/j.neurobiolaging.2014.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalar atrophy in symptomatic Alzheimer's disease based on diffeomorphometry: the BIOCARD cohort

Abstract: This paper examines the diffeomorphometry of MRI derived structural markers for the amygdala, in subjects with symptomatic Alzheimer’s disease (AD). Using linear mixed-effects models we show differences between those with symptomatic AD and controls. Based on template centered population analysis, the distribution of statistically significant change is seen in both the volume and shape of the amygdala in subjects with symptomatic AD compared to controls. We find that high-dimensional vertex based markers are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
41
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 38 publications
9
41
0
Order By: Relevance
“…According to our vertex-based shape analysis, we observed significant, regionally specific, surface area atrophies on both the bilateral hippocampi and the bilateral amygdalas, which is also consistent with the shape findings obtained from our previous studies [20,23] as well as other studies [1519,21,26], although shape analyses of the amygdala are less common than those of the hippocampus.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to our vertex-based shape analysis, we observed significant, regionally specific, surface area atrophies on both the bilateral hippocampi and the bilateral amygdalas, which is also consistent with the shape findings obtained from our previous studies [20,23] as well as other studies [1519,21,26], although shape analyses of the amygdala are less common than those of the hippocampus.…”
Section: Discussionsupporting
confidence: 92%
“…5 and 6), the localized surface area atrophy in the right amygdala is more wide spread than that in the left amygdala, with the main subregions affected being the basolateral and basomedial components. A thorough survey of the AD literature would suggest that there have been very few published amygdalar subfield morphometric analyses, with [69] being the sole example outside of previous studies by the current authors' research groups [20,23,24]. A direct comparison with the findings reported in [69] is challenging given that the subdivision criteria of the amygdalas were rather different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrophy has been found to be associated with impaired neurologic and neurocognitive performance. [7][8][9][10] More recently, research revealed that deep GM atrophy specifically plays an important role in the characterization, course, and progression of AD [11][12][13][14][15][16][17] and in other diseases like MS [18][19][20] and Parkinson disease. [21][22][23] Measurements of deep GM atrophy could therefore be of importance in the evaluation of neuroprotective treatment (eg, in investigating drug efficacy).…”
mentioning
confidence: 99%
“…By using the fMRI method, this study focused on amygdale segmentation and proposed its accu-rate functional disconnection pattern in the AD patients. Recent researches on AD have shown that altered structure and function of amygdale, which provided a promising indicator of AD [17]. However, previous studies often considered the amygdale as a single structure [18], and little is known about the functional connectivity changes of amygdale subregions in AD subjects.…”
mentioning
confidence: 99%